Tax Incentives and Job Creation in the Tourism Industry of Brazil - Grégoire Garsous; David Corderi Novoa; Mercedes Velasco (Inter-American Development Bank (IDB), 2015)
In recent decades, a significant number of developing countries have implemented fiscal incentives programs for the tourism industry as part of their regional development policies. The main objective of these programs is to increase local investment and employment, as tourism activities are labor intensive. Little evidence is available, however, to assess the effect of these policies on job creation. This paper analyzes a fiscal incentives program that the Brazilian federal government introduced in 2002 to develop the tourism industry in the undeveloped region of Northeast Brazil. It provides evidence that income tax credits had a significant positive effect on job creation. We find that local employment in the tourism industry was on average 34 percent higher in those municipalities that benefited from the program.
hdl:11319/7324
Keywords: H25; H71; L83; R58; Z32; 330; local public economies; regional development; tax incentives; tourism; employment